2001
DOI: 10.1111/1468-2230.00339
|View full text |Cite
|
Sign up to set email alerts
|

Career Paths and Choices in a Highly Differentiated Profession: The Position of Newly Qualified Solicitors

Abstract: Differences in the working lives of solicitors have become increasingly marked in recent years. Growing numbers of lawyers are employed in the public and corporate sectors and, with the increasing size and wealth of City of London commercial firms, there are significant differences between these firms and thosè high-street' firms that serve local communities. These differences impact on lawyers throughout training and beyond, both in terms of rites of passage into the profession and in conditions of employment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…In one of the original studies of lawyers' job satisfaction, Hirsch (1985) reported on a random probability survey of lawyers in the United States finding that overall levels of reported satisfaction were high (68 percent of respondents were very or somewhat satisfied with their current job). Similar results have been found from research surveying lawyers across the country (Hirsch 1985, Tucker et al 1989Chambers 1989) and in particular cities or regions (Taber et al 1988;Gellis 1991;Adams 1994;Hagan & Kay 1995;Lempert et al 2000;Heinz et al 2005;Boon et al 2001). Yet the popular press, along with some academic work, continues to proclaim that law is a dissatisfying career (e.g., Tazian 2005;Pedone 2004;Ranalli 2003;''Lawyers Express Dissatisfaction with Stress Levels and Long Working Hours, Survey Shows,'' National Post, 6 April, p. C7;Eviatar 2000).…”
Section: Satisfaction Debatessupporting
confidence: 73%
See 1 more Smart Citation
“…In one of the original studies of lawyers' job satisfaction, Hirsch (1985) reported on a random probability survey of lawyers in the United States finding that overall levels of reported satisfaction were high (68 percent of respondents were very or somewhat satisfied with their current job). Similar results have been found from research surveying lawyers across the country (Hirsch 1985, Tucker et al 1989Chambers 1989) and in particular cities or regions (Taber et al 1988;Gellis 1991;Adams 1994;Hagan & Kay 1995;Lempert et al 2000;Heinz et al 2005;Boon et al 2001). Yet the popular press, along with some academic work, continues to proclaim that law is a dissatisfying career (e.g., Tazian 2005;Pedone 2004;Ranalli 2003;''Lawyers Express Dissatisfaction with Stress Levels and Long Working Hours, Survey Shows,'' National Post, 6 April, p. C7;Eviatar 2000).…”
Section: Satisfaction Debatessupporting
confidence: 73%
“…Most research similarly tries to parcel out satisfaction by asking whether certain groups within the barFin particular, women and minority lawyersFare where one finds dissatisfaction within the profession. Here too, however, researchers have been stymied: women (Taber et al 1988;Chambers 1989;Tucker et al 1989;Gellis 1991;Hagan & Kay 1995;Dau-Schmidt & Mukhopadhaya 1999;Lempert et al 2000:486, Table 33;Reichman & Sterling 2004;Heinz et al 2005;Boon et al 2001) and minority lawyers (Dau-Schmidt & Mukhopadhaya 1999;Lempert et al 2000;Heinz et al 2005) continue to report high rates of overall job satisfaction, even if they are less satisfied with certain aspects of their workplace or certain elements of lawyering. Since women and minority lawyers do not, in fact, enjoy the success of white male lawyers (e.g., Hagan & Kay 1995;Wilkins 1999;Chambliss 2000), this has led to a ''paradox'' of satisfaction (Hull 1999) that researchers continue to investigate.…”
Section: Satisfaction Debatesmentioning
confidence: 99%
“…Barry 2005; Robinson and Casalino 1996) medium‐sized practice or network of generalists, such as teaching colleges, city law firms, general hospitals or multi‐site practices – in partnership, local network or group practice (e.g. Boon et al. 2001; Lee and Pennings 2002) large generalist firms, networks of generalists or franchises, such as national law firms, large general hospitals or franchised dental clinics (e.g.…”
Section: Towards a Typology Of Professional Organizationsmentioning
confidence: 99%
“…medium‐sized practice or network of generalists, such as teaching colleges, city law firms, general hospitals or multi‐site practices – in partnership, local network or group practice (e.g. Boon et al. 2001; Lee and Pennings 2002)…”
Section: Towards a Typology Of Professional Organizationsmentioning
confidence: 99%
“…6 Rolfe and Anderson (2003). 7 Boon, Duff, and Shiner (2001), Boon, Flood and Webb (2005). 8 Seron (1992).…”
mentioning
confidence: 99%